Using the Power of Narratives in E-Learning for COVID-19 Vaccine Hesitancy Conversations: A Mixed Methods Study in Medical Education [version 2; peer review: 2 approved] - Aayushi Gupta; Graham Easton; Anita Berlin (MedEdPublish)
Background During the COVID-19 pandemic, we developed an e-learning resource to support medical students in having effective conversations with COVID vaccine hesitant patients (an urgent challenge). Development of information and communication skills elements was underpinned by narrative learning theory; learners interact with three fictional characters whose stories run through the resource in activities and role-plays. We co-developed the resource and characters with students, colleagues and local community. Methods We used a mixed methods approach to evaluate the resource, including a survey of pre- and post- module self-confidence scores, and by thematic analysis of a focus group with seven final year medical students to explore their perceptions of how the story elements influenced their learning. Results All students surveyed reported an improvement in their confidence in having effective conversations with vaccine-hesitant patients. The focus group analysis suggests that character-based narratives can promote learning online, particularly through engagement and accessibility, relatability of characters and their stories, improved memory, and emotional connection. Conclusions This study suggests that character-driven stories have potential value in online learning about vaccine hesitancy conversations. Further research is needed to establish the nature of their impact on different aspects of learning including the duration of effect on students' communication skills and any patient-related outcomes.